Pendampingan Pemasaran dan Penyusunan Laporan UMKM Binaan FEB UP I Made Instant Food - Chasbiandani, Tryas; Utami, Khalida; Riskarini, Dian; Rosdiana, Elly; Nabila, Vibi Dwita (SULUH: Jurnal Abdimas, 2023)
The purpose of community service is to provide assistance for level improvement (Scale Up) related to Marketing management and Financial Management at MSMEs assisted by FEB UP I Made Instant Food. This method of implementing Community Service uses training and mentoring methods by the Community Service team. The result of this assistance is the creation of an Instagram account for marketing and preparation of reports on the cost of goods produced, cost of goods sold and profit and loss of business I Made Instant Food